Evaluation of STEM Education by Turkish Science Teachers - HÜLYA ASLAN EFE; Kadri Hanas (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
STEM education has been adopted all around the world to educate individuals that meet the requirements of the changing workforce. Currently, efforts to integrate STEM education into mainstream education are being made in Turkey as well, and it is critical to review them. Therefore, the aim of the current study is to obtain an evaluation of the developing STEM education in Turkey by science teachers. For this purpose, the surveying method, one of the quantitative research methods, was used. 128 science teachers working in Diyarbakır province participated in the study. The “Criteria for Quality STEM” scale, adapted to Turkish by the researchers, was used as the data collection tool in the study. Based on the results, it was concluded that young teachers have higher score averages in improving relations between school, society and business world. It was also found that teachers who practice STEM in science education by spreading them over a period of time have higher averages in terms of creating a STEM culture and climate and establishing the connection between school, society and business world. It was determined that teachers who read academic studies have higher averages in integration of academic knowledge and providing school, community and cooperation compared to those who do not. It was determined that the teachers who previously took part in projects related to STEM education have higher averages in creating the STEM culture and climate in schools. In the light of these results, it is suggested that future research is needed to help science teachers learn how to implement STEM education in their classes so that they can use it effectively and successfully.